2022
DOI: 10.1017/s0007485322000608
|View full text |Cite
|
Sign up to set email alerts
|

Do primary and secondary host plants affect aphid- parasitoid interactions in fruit orchards?

Abstract: The aim of this study was to investigate how the primary (PHP) and secondary host plants (SHP) in the fruit orchards affect the interactions of aphids and their parasitoids in northwest Turkey during spring and summer 2020 and 2021. In total, 67 tritrophic aphid–parasitoid-host plant interactions, including new association records for Europe and Turkey, were obtained from 16 parasitoid species from the subfamily Aphidiinae (Hymenoptera: Braconidae) reared from 25 aphid species (Hemiptera: Aphididae) on 22 PHP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
(77 reference statements)
1
0
0
Order By: Relevance
“…This is likely due to increased access to floristic resources and nest sites associated with increased tree and crop richness but also due to the high abundance of other invertebrate species [53]. Our finding is further bolstered by Kök et al [54], who explains that the use of non-crop plant species within agricultural environments can support conservation biological control. The preservation of the abundance of Hymenopterans contributing to biological control, many of which are parasitoids, is essential within complex polyculture and rustic systems, as by promoting invertebrate abundance and richness through agroecological practices, populations of crop pest species can also increase, as we found with the populations of Coleoptera (which included potential pests such as individuals from the families Chrysomelidae, Ptinidae, and Scarabaeidae), Hemiptera (in the study area, we found individuals from families that are considered pests, such as Dictyopharidae, Fulgoridae, Pentatomidae, and the subfamily Triatominae), and Orthoptera [53,55,56].…”
Section: The Effect Of Cropland Managementsupporting
confidence: 52%
“…This is likely due to increased access to floristic resources and nest sites associated with increased tree and crop richness but also due to the high abundance of other invertebrate species [53]. Our finding is further bolstered by Kök et al [54], who explains that the use of non-crop plant species within agricultural environments can support conservation biological control. The preservation of the abundance of Hymenopterans contributing to biological control, many of which are parasitoids, is essential within complex polyculture and rustic systems, as by promoting invertebrate abundance and richness through agroecological practices, populations of crop pest species can also increase, as we found with the populations of Coleoptera (which included potential pests such as individuals from the families Chrysomelidae, Ptinidae, and Scarabaeidae), Hemiptera (in the study area, we found individuals from families that are considered pests, such as Dictyopharidae, Fulgoridae, Pentatomidae, and the subfamily Triatominae), and Orthoptera [53,55,56].…”
Section: The Effect Of Cropland Managementsupporting
confidence: 52%